Bacterial healing of cracks in metakaolin-based geopolymer concrete exposed to high temperatures - Tanyildizi, Harun; Ziada, Mahmoud; Uysal, Mucteba; Erdem, Savas (WILEY, 2026)
This study examined the bacterial healing of metakaolin-based geopolymer concrete modified with colemanite (K) and red mud (RM) exposed to high temperatures. The metakaolin-based geopolymer concrete samples modified with 4% K and 6% RM were prepared. Then, the geopolymer concretes were subjected to 200, 400, 600, and 800 degrees C to form high-temperature cracks. Also, half of these samples were cracked when loaded to 70% of their tensile strength. Then, these cracks developed in the specimens subjected to varying temperatures healed using Sporosarcina pasteurii. The healing was conducted by injecting the bacterial medium into the cracks. Weight change, ultrasonic pulse velocity, split tensile strength, and water absorption experiments were performed on healed samples and control specimens subjected to high temperatures. Also, various microstructural analyses and micro-computed tomography analyses were conducted to examine the healing performance of S. pasteurii and the development of calcium carbonate. This study found that the recovery percentages of split tensile strength of specimens exposed to high temperatures ranged between 84.60% and 21.17%. Also, this study found that S. pasteurii can successfully heal 98.86% of high-temperature cracks.
Keywords: geopolymer concrete; healing; high-temperature cracks; metakaolin; Sporosarcina pasteurii; SPOROSARCINA-PASTEURII; FLY-ASH; CARBONATE PRECIPITATION; DURABILITY; EVOLUTION; UREOLYSIS; UREASE; Construction & Building Technology; Engineering